Keys to the critical analysis of historical discourse (2024)
Objective: To offer a methodological proposal for the critical analysis of historical discourse (CDAH) from an interdisciplinary perspective. Originality/contributions:  The integration in the analytical-interpretative horizon of theoretical and methodological principles of critical discourse analysis with decolonial studies and Bakhtin's hermeneutics around the conception and representation of socio-cultural actors in historical discourse. Method: Based on the socio-cognitive, semiotic and historical approaches of critical discourse studies, the analysis is carried out in three phases: nominalization, predication and argumentative schemes that justify the conception and representation of sociocultural actors. Data collection strategies:  ten chronicles on the “Discovery” and “Conquest” of the New World” were taken; and for the examination of textual data the tools Nvivo, T-LAB 7.5 were used. Conclusions: the integration of critical discourse studies (CDS) with decolonial studies (DE) and Bakhtin's hermeneutics (HB) enables a critical understanding that overcomes the predominant Eurocentric conceptions of the historical discourse on the facts related to the “discovery” and the “Conquest” of the New World.